# Solve: y^2 - y - 30 = 0

*print*Print*list*Cite

### 3 Answers

The equation to be solved is: y^2 - y - 30 = 0

y^2 - y - 30 = 0

=> y^2 - 6y + 5y - 30 = 0

=> y(y - 6) + 5(y - 6) = 0

=> (y + 5)(y - 6) = 0

y + 5 = 0

=> y = -5

y - 6 = 0

=> y = 6

**The solution of the equation is y = -5 and y = 6**

We'll apply quadratic formula to solve the equation:

y1 = [-(-1)+sqrt((-1)^2 - 4*1*(-30))]/2*1

y1 = (1 + sqrt121)/2

y1 = (1+11)/2

y1 = 12/2

y1 = 6

y2 = (1-11)/2

y2 = -10/2

y2 = -5

**The solutions of the quadratic are: {-5 ; 6}.**

The equation y^2 - y - 30 = 0 has to be solved.

y^2 - y - 30 = 0

y^2 - 2*(y/2) - 30 = 0

y^2 - 2*(y/2) + 1/4 - 30 - 1/4 = 0

(y - 1/2)^2 - 121/4 = 0

(y - 1/2)^2 = 121/4

y - 1/2 = +- 11/2

y = 1/2 + 11/2 = 12/2 = 6

y = 1/2 - 11/2 = -10/2 = -5

The solution of the equation y^2 - y - 30 = 0 is y = 6 and y = -5